BS EN ISO 11806-1. Agricultural and forestry machinery. Safety requirements and testing for portable, hand-held, powered brush-cutters and grass-trimmers. Part 1. Machines fitted with an integral combustion engine (18th June 2020) - British Standards Institution,
No abstract available